Negative-pressure wound therapy compared with standard dressings following surgical treatment of major trauma to the lower limb: the WHiST RCT - Costa, M; Achten, J; Knight, R; Png, M; Bruce, J; Dutton, S; Madan, J; Vadher, K; Dritsaki, M; Masters, J; Spoors, L; Campolier, M; et al. (NIHR Journals Library, 2020)
Background: Major trauma is the leading cause of death in patients under 45 years. Patients with major trauma usually have lower limb fractures. Surgery to fix the fractures is complicated and the risk of infection may be as high as 27%. The type of dressing applied after surgery could potentially reduce the risk of infection. Objectives: To assess the deep surgical site infection (SSI) rate, disability, quality of life, patient assessment of the surgical scar and resource use in patients with surgical incisions associated with fractures following major trauma to the lower limbs, treated with incisional negative-pressure wound therapy (NPWT) versus standard dressings. Design: A pragmatic, multicentre randomised controlled trial. Setting: Twenty-four specialist trauma hospitals representing the UK Major Trauma Network. Participants: 1548 adult patients were randomised from September 2016 through April 2018. Exclusion included presentation more than 72 hours after injury and inability to complete questionnaires. Interventions: NPWT (n=785), where a non-adherent absorbent dressing covered with a semi-permeable membrane is connected to a pump in order to create a partial vacuum over the wound, versus standard dressings not involving negative pressure (n = 763). Trial participants and the treating surgeon could not be blinded to treatment allocation. Main outcome measures: Deep SSI at 30 days was the primary outcome measure. Secondary outcomes were: deep infection at 90 days, Disability Rating Index, health-related quality of life (EQ-5D), patient self-assessment of the surgical scar and resource use collected at three and six months post-surgery. Results: 98% of participants provided primary outcome data. There was no evidence of a difference in the rate of deep SSI at 30 days. The infection rate was 6.7% (50/749) in the standard dressing group and 5.8% (45/770) in the NPWT (Intention to treat Odds Ratio (OR) 0.87; 95% Confidence Interval (CI) 0.57 to 1.33, p=0.52). There was no difference in the deep SSI rate at 90 days; 12.8% in the standard dressing group and 11.4% in the NPWT (OR 0.86; 95% CI 0.61, 1.23, p=0.41). There was no difference between the two groups in disability, quality of life or scar appearance at three or six months. NPWT did not reduce the cost of treatment and was associated with a low probability of cost-effectiveness. Limitations: Owing to the emergency nature of the surgery, we anticipated that some patients who were randomised would subsequently be unable or unwilling to participate. However, the majority of the patients (85%) agreed to participate. Therefore, participants were representative of the population with lower limb fractures associated with major trauma. Conclusions: Incisional NPWT does not provide a clinical nor economic benefit to patients with surgical incisions associated with major trauma to the lower limbs. Future work: Our worksuggests that the use of incisional NPWT dressings in other at-risk surgical wounds requires further investigation. Future research may also investigate different approaches to reduce post-operative infections, for example the use of topical antibiotic preparations in surgical wounds and the role of orthopaedic implants with antimicrobial coatings when fixing the associated fracture.